Variation in Congenital Heart Surgery Costs Across Hospitals - Pasquali, Sara K. (American Academy of Pediatrics, 2014)
BACKGROUND: A better understanding of costs associated with common and resource-intense conditions such as congenital heart disease has become increasingly important as children’s hospitals face growing pressure to both improve quality and reduce costs. We linked clinical information from a large registry with resource utilization data from an administrative data set to describe costs for common congenital cardiac operations and assess variation across hospitals. METHODS: Using linked data from The Society of Thoracic Surgeons and Pediatric Health Information Systems Databases (2006–2010), estimated costs/case for 9 operations of varying complexity were calculated. Between-hospital variation in cost and associated factors were assessed by using Bayesian methods, adjusting for important patient characteristics. RESULTS: Of 12 718 operations (27 hospitals) included, median cost/case increased with operation complexity (atrial septal defect repair, [$25 499] to Norwood operation, [$165 168]). Significant between-hospital variation (up to ninefold) in adjusted cost was observed across operations. Differences in length of stay (LOS) and complication rates explained an average of 28% of between-hospital cost variation. For the Norwood operation, high versus low cost hospitals had an average LOS of 50.8 vs 31.8 days and a major complication rate of 50% vs 25.3%. High volume hospitals had lower costs for the most complex operations. CONCLUSIONS: This study establishes benchmarks for hospital costs for common congenital heart operations and demonstrates wide variability across hospitals related in part to differences in LOS and complication rates. These data may be useful in designing initiatives aimed at both improving quality of care and reducing cost.